Job quality in triadic employment relations: Work attitudes of Norwegian temporary help agency employees. Issue 3 (September 2015) - Kalleberg, Arne L.; Nesheim, Torstein; Olsen, Karen M.
Highlights We examine job quality among employees of temporary help agencies (THA). We assess how triadic employment relations influence work attitudes. Job quality is greater when the employees are valuable to the client-firm. Conflicting signals from THAs and clients reduce job satisfaction. Preferences for temporary work are strongly associated with job satisfaction.